Astronomi Islam Era Dinasti Mamalik (1250-1517) - Arwin Juli Rakhmadi (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2013)
Astronomy is special scientific discipline in Islam as it relates to daily Muslim worship practices. In the Mamalik era (1250-1517), especially in Cairo and Damascus regions, Islamic astronomy has developed significantly as can be seen in the new discoveries of astronomical instruments. However, Islamic astronomy in the era of Mamalik conceals a very large amount of scientific knowledge that needs further discussion. As mentioned by King, there were a dozen of Islamic schbolars in astronomy whose treatises and ideas are unrevealed. Therefore contemporary astronomical studies run in higher educational institutions, should also seriously be focused on examining classical knowledge in astronomy. This article discusses the history and develop- ment of Islamic astronomy in the era of Mamalik and their contribution to the body of scientific knowledge in as- tronomy in that period